Persepsi Mahasiswa Tentang Perkuliahan Berbasis E-Learning dengan Menggunakan Schoology - Patrisius Afrisno Udil (Universitas Nusa Cendana, 2020)
This research aims to describe perception of mathematics education students at Nusa Cendana University about e-learning course using schoology. It also describes students’ perception based on aspects and indicators of perception. It is descriptive quantitative research with survey method. Research sample consist of 41 students of semester 6 chosen with simple random sampling. The research was held on second semester of 2019/2020 academic year. Data collection was held by using instrument namely students perception scale. Data was analysed with descriptive statistics and then the findings was described. The results of this research indicate that (1) generally students’ perception was identified in very high (very positive) category with average score is 73, 39; (2) students’ perception was identified in very high (very positive) category for aspect schoology as media and in high (positive) category for aspect e-learning course quality; (3) students’ perception was identified in very high (very positive) category for all indicators of first aspect. For second aspect, it was identified in very high (very positive) category for 2 indicators and in high (positive) category for 2 others.